Women's Bodies and Medical Science - Bryder, L. author. aut Link
VI, 250 p.
Keywords: An analysis of a scandal involving a doctor accused of allowing a number of women to develop cervical cancer from carcinoma in situ as part of an experiment he had been conducting since the 1960s into conservative treatment of the disease, to more broadly explore dramatic changes in medical history in the second half of the twentieth century.